Research on the mechanism of AI service satisfaction based on the culture and AI strategy perspective. - Du, Shiqi (2020)
Abstract In the service industry, using artificial intelligent robots to replace service staffs in the service process has become a fashionable topic. The traditional service mode of service industry has changed a lot with the rapid development of science and technology. The artificial intelligent robot is considered as a new service carrier which entered the public’s view in recent years. Nevertheless, there are little literatures which explored on the psychological changes of consumers if service staffs are replaced by artificial intelligent robots in the service industry. Furthermore, the literatures which explore the possible impact on service quality and satisfaction if service staffs are replaced by artificial intelligent robots are insufficient as well. To fill the gap in the research of service industry, this research mainly focuses on two independent variables. The first independent variable is cultural variable (eastern culture and western culture), in this research, Chinese consumers are treated as the sample of eastern culture, American consumers are treated as the sample of western culture. The other independent variable is AI service strategy (manned strategy and unmanned strategy), manned strategy refers to the service is mainly provided by the artificial intelligent robots under the intervention of service staffs, in contrast, unmanned strategy refers to the service only provides by the robots in the whole process. The result of the research is obtained through the scenario simulation experiment, the findings show that unmanned strategy brought consumers higher fear and higher loss of control than manned strategy, furthermore, consumers under western culture feel higher degree of fear and loss of control than consumers under eastern culture when facing the services by artificial intelligent robots. This research also confirms that perceived fear, loss of control and perceived service quality influence the satisfaction of AI service. Keywords：AI robots, AI service satisfaction, AI service quality, perceived fear, loss of control, culture，manned/unmanned strategy